Design of an electronic election system using blockchain technology - Tkačik, Vladislav; Bruckner, Tomáš, 1974-; Karkošková, Soňa; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
This thesis deals with e-voting and designing an appropriate e-voting system based on blockchain technology for elections in the Czech Republic and its Parliament election. This thesis consists of a research of e-voting systems and a practical part, which consists of designing the voting system itself. In the first part, the first goal is to provide information and knowledge upon which the practical part of this thesis is based on. The author will acquire this information by an in-depth analysis of electronic voting and by studying already realised e-voting systems as well as voting systems based on blockchain and also their design proposals. The second goal is to create a suitable design of a voting system based on blockchain by using knowledge acquired in the first part.
Vedoucí práce: Tomáš Bruckner
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses